Full factorial study of pipe characteristics, stagnation times, and water quality. Issue 5 (14th October 2020) - Tolofari, Dienye L.; Masters, Sheldon V.; Bartrand, Tim; Hamilton, Kerry A.; Haas, Charles N.; Olson, Mira; Summers, R. Scott; Rasheduzzaman, Md; Young, Audrey; Singh, Rajveer; Gurian, Patrick L.
Abstract: This study examines the effect of pipe characteristics and stagnation time on nitrification, disinfectant loss, and organic carbon concentrations. Pipe racks consisting of different pipe materials (chlorinated polyvinyl chloride [CPVC], cross‐linked polyethylene [PEX‐B], and copper), diameters (0.75 and 0.5 in.), and water stagnation times (1 week and 12 hr) were set up in two cities with different disinfectants (chloramine and free chlorine) and different corrosion control (orthophosphate vs. pH/alkalinity adjustment). Copper pipe material had lower residual concentrations relative to plastic pipe in both water systems. In the chloramine system, residual concentrations were lower for smaller‐diameter pipes, whereas diameter did not strongly influence residual concentration in the chlorine system. Total organic carbon (TOC) increased during stagnation in the chloramine system. Nitrification was observed in the chloramine system for stagnation times of 1 week and 12 hr, indicating that flushing as frequently as every 12 hr may not be an effective mechanism for nitrification control in building plumbing.